JURNALISME DAN WAWANCARA KURSI KOSONG MENTERI TERAWAN (ANALISIS SEMIOTIKA ROLAND BARTHES DALAM EPISODE WAWANCARA KURSI KOSONG MATA NAJWA TAHUN 2020) - Ressa Seftiana; Abdul Fadli Kalaloi (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
Journalism on television is present as a bridge for society in fulfilling everyone's right to obtain information that is in accordance with the facts. Senior journalist Najwa Shihab came with a different spectacle that had never happened in Indonesia, he presented an interview with an empty chair. This study uses a constructivist paradigm with descriptive qualitative research methods through the semiotic approach of Roland Barthes. The purpose of this study is to describe how the vacant seat interview show